Impact of organizational diversity on safety culture and performance in PT. UVW Indonesia - Nasarasiddi, Katami (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study examined the influence of organizational diversity on safety culture and performance in PT. UVW is a global chemical company based in Indonesia. Utilizing the Cultural Intelligence (CQ) framework, Social Identity Theory, and Resource-Based View (RBV), this study investigates how different employee backgrounds affect safety outcomes. Method: By employing an approach that integrates qualitative interviews with quantitative KPI analysis, this study demonstrates that diversity improves safety culture through various perspectives and innovative solutions. Nonetheless, to maximize these benefits, it is essential to address challenges, such as communication barriers and conflicts. Result: The findings highlight that effective diversity management, inclusive communication, comprehensive training, and strong leadership within a diverse organizational demography of gender, age, work tenure, and educational background are vital for cultivating a positive safety culture. The research emphasizes that when strategically managed, organizational diversity can be a significant asset, enhancing safety performance and creating a safer and more efficient workplace. This research offers practical insights for multinational companies seeking to leverage diversity while overcoming the associated challenges to boost safety culture and performance. Conclusions: Organizational diversity, when managed strategically with inclusive leadership and comprehensive training, serves as a valuable asset that strengthens safety culture and enhances organizational performance. Limitations: This study was limited to PT. UVW’s manufacturing site in Indonesia and relied on self-reported data, which may restrict the generalizability of results. Contribution: The study provides practical insights for multinational companies on leveraging diversity to improve safety outcomes and theoretical contributions by applying CQ, Social Identity Theory, and RBV to workplace safety research.